Pre-cueing, the Epistemic Role of Early Vision, and the Cognitive Impenetrability of Early Vision - Raftopoulos, Athanassios (Frontiers in Psychology, 2017)
I have argued (Raftopoulos 2009, 2014) that early vision is not directly affected by cognition since its processes do not draw on cognition as an informational resource; early vision processes do not operate over cognitive contents, which is the essence of the claim that perception is cognitively penetrated; early vision is cognitively impenetrable. Recently it has been argued that there are cognitive effects that affect early vision, such as the various pre-cueing effects guided by cognitively driven attention, which suggests that early vision is cognitively penetrated. In addition, since the signatures of these effects are found in early vision it seems that early vision is directly affected by cognition since its processes seem to use cognitive information. I defend the cognitive impenetrability of early vision in three steps. First, I discuss the problems the cognitively penetrability of perception causes for the epistemic role of perception in grounding perceptual beliefs. Second, I argue that whether a set of perceptual processes is cognitively penetrated hinges on whether there are cognitive effects that undermine the justificatory role of these processes in grounding empirical beliefs, and I examine the epistemic role of early vision. I argue, third, that the cognitive effects that act through pre-cueing do not undermine this role and, thus, do not render early vision cognitively penetrable. In addition, they do not entail that early vision uses cognitive information.